Methodology for Assessing the Quality of Rail Connections on the Network - Gasparik, Jozef; Siroky, Jaromir; Peceny, Lumir; Halas, Martin (Communications - Scientific letters of the University of Zilina, 2014)
The role of the EU transport system is to provide a high degree of mobility where necessary, to increase its performance in terms of speed, comfort, and safety. Achieving a consistent, integrated, and efficient transport system currently requires connections linking all transport modes. The most important criteria from the point of view of passengers are the reachability of the destination and frequency. This paper assesses the quality of rail services by considering the supply of connections on the network. It proposes a methodology for evaluating the constructed timetable in passenger traffic for the assessment of the achievability of tariff points. We also present some results of a case study of a Slovakian railway network.